Clinical Cohort Study in Canine Patients, to Determine the Average Platelet and White Blood Cell Number and Its Correlation with Patient’s Age, Weight, Breed and Gender: 92 Cases (2019–2020) - Isabel de Marcos Carpio (MDPI AG, 2021)
Due to its easy preparation and that it is well tolerated, the use of autologous platelet-rich plasma (PRP) has become increasingly popular in regenerative medicine. However, there are still no clear guidelines on how it should be classified or whether the individual canine patient’s clinical status can influence its quality. Objective: This study aims to show if the weight, age, sex, neutered status or breed of canine patients have any correlation with the composition of PRP. Design: A blinded count of the platelets and white blood cells (WBC) was performed from 111 samples from 92 client owned dogs undergoing treatment for degenerative joint disease (DJD). The results were analysed using Pearson correlation test, ANOVA test or Student T-test. Results: There is a positive correlation between the number of platelets and WBC in canine patients of different breeds, but there was no significant difference on the platelet number and WBC number among the different breeds. The weight of the patient is also directly correlated to the platelet number (p = 0.003) but not WBC number. WBC number was negatively correlated to the weight of the patient. The sex and age of the patient did not affect platelets and WBC number, although WBC number is increased in non-neutered male population (p = 0.003). However, it would be interesting to investigate whether the growth factors released from the platelet granules are affected by patient variables in a canine population. Conclusions: Our results show that it is possible to obtain good quality autologous PRP, irrespective of age, sex, neutered status or weight of the patient, for PRP regenerative therapy.